Strategy and Positioning on the Local Cuisine of Suratthani Province - ทวีพงษ์, พรทิพย์ (Journal of Management Sciences Suratthani Rajabhat University, 2017)
This research is a part of the Study on The Local Wisdom of Food in Suratthani Province. The objective is to study local wisdom products in order to find ways to develop products and to create a sustainable local wisdom associated with the context, process manufacturing, value and worth of the products. Sales and marketing strategies were created based on interviews the elderly people who have local wisdom knowledge in the area in order to obtain information and set the stage for the selection of local community food.Derived food lists were then synthesised by interviewing prominent, well known and experienced local food producers in the province. Content analysis was used to analysis and descriptive results were presented. The findings show that local wisdom food of Bansuan Zone (Banna - Doem, Bannasearn, Weing - Sa, Prasang and Chaiburi) are Pung Pla, Kowyum Samunprai, Yum Bi - Mei, Lap Lin Fah and Aub Pla Preaw. It creates a selling point and a marketing strategy that does not focus on food culture and a marketing strategy to promote the market. Even if some food products will be produced for commercial purposes, a point often made by market segmentation is to provide products with more variety so consumers have a choice in their dietary preferences. Advertising uses writing on the menu of the restaurant or if the food is sufficiently known, it is a label on the packaging box or bag.